The Effect of Augmented Reality-Assisted BELKOPATA on Elementary School Students’ Learning Achievement and Critical Thinking Skills - Maya Eka Purwanti; Siti Mas’ula; Punaji Setyosari; Slamet Arifini; Riska Pristiani (Researchparks Publishing, 2026)
Digital transformation requires learning media that can visualize abstract concepts while supporting the development of higher-order thinking skills. This study aimed to analyze the effects of BELKOPATA learning media supported by Assemblr EDU on elementary school students’ learning achievement and critical thinking skills, both separately and simultaneously. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design. The participants were 37 students, comprising 17 students in the control class and 20 students in the experimental class. The experimental class received instruction using BELKOPATA supported by Assemblr EDU, whereas the control class received instruction without this media. Learning achievement data were collected through pretests and posttests, while critical thinking skills were assessed using an observation sheet covering information analysis, reasoning, evidence evaluation, problem solving, and conclusion drawing. The instruments were tested for validity and reliability before use. Data were analyzed using descriptive statistics, the Shapiro Wilk test, Levene’s Test, Box’s M Test, and Multivariate Analysis of Variance. The MANOVA results showed a significant simultaneous difference in learning achievement and critical thinking skills between the two classes, with Pillai’s Trace=0.332, F(2,34)=8.443, and p=0.001. Separately, the experimental class achieved significantly higher learning outcomes than the control class, F(1,35)=15.449, p<0.001, with partial eta squared=0.306. However, the difference in critical thinking skills was not significant, F(1,35)=2.326, p=0.136. The multivariate effect was therefore driven primarily by learning achievement. Therefore, BELKOPATA supported by Assemblr EDU effectively improved learning achievement, although its influence on critical thinking requires longer intervention and more intensive analytical activities.